Testing for Competition in Serbian Banking Industry: the Panzar-Rosse Approach - Babić, Aljoša; Zildžović, Emir; Lončar, Dragan (Industrija, 2015)
The level of competitiveness in Serbian banking industry is tested using the Panzar-Rosse model on bank level data in period from 2004 to 2012. The panel estimation results imply monopolistic competition in the entire banking sector. We find that large banks, which comprise more than 65% of total banking sector assets exhibit monopoly or strong oligopoly behaviour with perfect collusion. This implies that the prices of the banking products are suboptimal in terms of general welfare.